YES Problem: f(g(X)) -> g(f(f(X))) f(h(X)) -> h(g(X)) Proof: String Reversal Processor: g(f(X)) -> f(f(g(X))) h(f(X)) -> g(h(X)) Matrix Interpretation Processor: dim=3 interpretation: [1 1 1] [h](x0) = [0 0 0]x0 [0 0 0] , [1 0 0] [0] [f](x0) = [0 0 1]x0 + [0] [0 1 0] [1], [1 0 0] [g](x0) = [0 1 1]x0 [0 1 1] orientation: [1 0 0] [0] [1 0 0] [0] g(f(X)) = [0 1 1]X + [1] >= [0 1 1]X + [1] = f(f(g(X))) [0 1 1] [1] [0 1 1] [1] [1 1 1] [1] [1 1 1] h(f(X)) = [0 0 0]X + [0] >= [0 0 0]X = g(h(X)) [0 0 0] [0] [0 0 0] problem: g(f(X)) -> f(f(g(X))) String Reversal Processor: f(g(X)) -> g(f(f(X))) Matrix Interpretation Processor: dim=3 interpretation: [1 1 1] [1] [f](x0) = [0 1 0]x0 + [0] [0 0 1] [0], [1 0 0] [0] [g](x0) = [0 1 1]x0 + [1] [0 1 1] [1] orientation: [1 2 2] [3] [1 2 2] [2] f(g(X)) = [0 1 1]X + [1] >= [0 1 1]X + [1] = g(f(f(X))) [0 1 1] [1] [0 1 1] [1] problem: Qed